2018
DOI: 10.1002/adfm.201805026
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Fabrication of Nanoporous Graphene for Ionic Separation Membranes

Abstract: Porous graphene membranes hold great promise for high-selectivity separation. Moreover, their practical application is limited by the lack of a simple and efficient method for the synthesis of porous graphene. Here, a rapid and scalable method is developed for the synthesis of porous graphene via partial combustion of graphene oxide imperfectly covered by hydrotalcite. This method is not only less energy-and time-intensive than existing ones, but also allows precise control of pore size. Remarkably, the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 37 publications
(53 reference statements)
0
44
0
Order By: Relevance
“…According to the previous report, the characteristic peak of the new phase can be indexed to the (003) plane of hydrotalcite ( Garcia-Gallastegui et al., 2012 ), which we define as Zn-hydrotalcite covering GO. In the previous work, theoretical calculation showed that a cyclic structure can be formed between nitrate ions and water molecules by hydrogen bonding ( Li et al., 2018 ). This distribution pattern leads to the formation of a layered structure of ions and water molecules parallel to the graphene surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous report, the characteristic peak of the new phase can be indexed to the (003) plane of hydrotalcite ( Garcia-Gallastegui et al., 2012 ), which we define as Zn-hydrotalcite covering GO. In the previous work, theoretical calculation showed that a cyclic structure can be formed between nitrate ions and water molecules by hydrogen bonding ( Li et al., 2018 ). This distribution pattern leads to the formation of a layered structure of ions and water molecules parallel to the graphene surface.…”
Section: Resultsmentioning
confidence: 99%
“…With the increase of the amount of Zn(NO 3 ) 2 from 300 g/L to 500 g/L, the peak position remains unchanged but its intensity shows a trend from rising to decline, reaching the highest point at 400 g/L. The effect may be attributed to an increase in the integral lateral area of hydrotalcite, and then a mass of emerging pores on the Zn-hydrotalcite surface reduces its crystallinity ( Garcia-Gallastegui et al., 2012 ; Li et al., 2018 ). These results also can be confirmed by transmission electron microscope (TEM) images as shown in Figures 1 D and S2 .…”
Section: Resultsmentioning
confidence: 99%
“…The nanopores of graphene membranes provide a significant pathway for ion penetration, therefore the ion selectivity facilitates the metal ion separation, Furthermore, the ion diffusion of porous graphene membranes can be enhanced by acid addition. To develop a metal ion separation performance, the pores of a graphene membrane can be modified by using oxide functional group derivatives [ 78 , 79 , 80 ]. The membrane modules often used in separation of mercury and heavy metals are hollow fibers and sheet layers [ 71 , 81 , 82 ].…”
Section: Membrane Separation For Mercury and Heavy Metalsmentioning
confidence: 99%
“…Hence, developing perforated graphene membranes (with pore sizes in the sub‐nanometer range) is necessary to enable the effective transport of molecules through graphene membranes. [ 201,202 ] This strategy is expected to reduce the energy barrier for molecular transport drastically without jeopardizing the extraordinary mechanical properties of graphene sheets, as single‐layer graphene can withstand a pressure difference of up to 6 atm. [ 12,99 ] In particular, the performance of functionalized graphene monolayers has been attempted to verify through a molecular dynamics simulation.…”
Section: Physicochemical Properties Of Graphene‐based Materialsmentioning
confidence: 99%